Application of Cognitive and Cyber Modelling for Cybersecurity Risk Management in Automated Process Control Systems - Lakhno, Valerii; Kasatkin, Dmytro; Mohylnyi, Hennadii; Desiatko, Alona; Zhyrova, Tetiana; Khorolska, Karyna; Kotenko, Nataliia (International Journal of Electronics and Telecommunications, 2026)
The growing number of cyber attacks in the world emphasises the importance of protecting critical computer systems (CCS), including automated process control systems (APCS). Ensuring the cybersecurity of CCSs becomes an essential element of resilience and reliability of modern information technologies. This paper considers the possibility of applying cognitive and cybernetic modelling and investigates the concepts that affect the cybersecurity risks of APCS. The methods of cognitive and cybernetic modelling made it possible to identify the links between the considered concepts, which made it possible to better understand the dynamics of changes in the system of APCS risk management.